A rare case of lung abscess due to esophageo-pulmonary fistula in asymptomatic carcinoma of esophagus - Ghosh, Soumitra; Handa, Neha; Tale, Sudheer; Bhalla, Ashish (Monaldi Archives for Chest Disease, 2021)
Acquired esophago-respiratory fistulae are usually esophago-tracheal or esophago-bronchial. Esophago-pulmonary fistulae are rare. Most patients present with cardinal symptoms of esophageal carcinoma or esophago-pulmonary fistula leading to early diagnosis. We report a 56-year-old female with an unusual presentation. She presented with high grade fever with chills and rigor, cough with mucopurulent expectoration and shortness of breath for 15 days without dysphagia, nausea, vomiting or chest pain. Clinically and radiologically a diagnosis of lung abscess was entertained and she was treated with multiple antibiotics without any improvement. Contrast Enhanced Computed Tomography (CECT) chest revealed esophageal malignancy with esophageal-pulmonary fistula communicating with abscess cavity. Patient responded to palliation with self-expandable esophageal stent and drainage of abscess. Although rare, asymptomatic malignant esophageal disease should be considered in the differential diagnosis of lung abscess, which does not follow a usual course. Keywords: Lung abscess, Esophageal cancer, Esophageo-pulmonary fistula, Self expandable metallic stent